OPTEXPLOR – new application for water resources management for private water supply utilities - Nunes, L. (2012)
This article presents the steps made for the development of a new water management system (WMS) for a private water utility in the south of Portugal, and its main results. The WMS is composed of a set of models representing the water resources, surface and groundwater, water quality models, economic models, and water allocation optimization models. The system was developed at the request of the regional water utility (Águas do Algarve, S.A.), which is responsible for distributing water to the entire Algarve region (most touristic area in Portugal, with about ten million tourists per year, and a local population of about four hundred thousand). Results clearly show that independently of the amount of water available, inter-annual exploration is always the best solution, if possible. When water scarcity is high, as in consecutive dry years, the water utility will need to call municipalities to use their systems to complement supply. The level of supply deficit is higher, in any case, for annual exploration management, and so are exploration costs. These results clearly show that water resources management needs careful inter-annual planning, even for a private water supply utility with very limited control over water exploration by other competing users.